A coordenação pedagógica na educação infantil: o trabalho observado e as perspectivas da coordenadora e das professoras de uma creche municipal - Pereira, Jorgiana Ricardo (2014)
The main objective of the present study is to investigate the work of the pedagogical coordination to observe their relationship with the faculty teaching practices, learning about the perspectives of teachers as well as the Educational Coordinator. The theoretical contributions were the pedagogy of early childhood education characterized by its specificity within the child pedagogy in general (ROCHA, 1999). The methodology is based in the principles of qualitative approach. Due to the interest to understand in depth the focused phenomenon, we chose the case study (LUDKE; ANDRÉ, 1986; YIN, 2010). The subjects were a pedagogical coordinator and four teachers from a full timemunicipal nursery school in Ceará. There were observations sessions with participants of the working daily life of the educational coordinator in the period of September to November 2013 and semi-structured individual interviews with the educational coordinator and teachers, focusing on their perceptions of the job of Education Coordination unit and their relationship with the faculty teaching practices. Data analysis showed that the daily work of teaching coordination in the researched institution relates little collaboratively to form good quality teaching practices by teachers and does not contribute to the construction of the particular professionalism of Early Childhood Education teachers. The perception of the educational coordinator about her work relies on the idea of love for the profession and to the children and shows confidence in its quality. On the other hand, the teachers consider that it does not meet their needs for guidance, monitoring and management of pedagogical work. Thus, considering the importance of the work of education coordination to build the quality of babies, small children and toddlers’ education in collective environments, it is so concluded that there is an urgent need to give more attention, technical and pedagogical support to the professional who is in charge of the pedagogical coordination of Early Childhood Education with a view of enhancing the quality of the work on the first stage of Early childhood education. The reality revealed in this study strengthens existing arguments that we need to think about the profile of the professionals who operates in kindergarten, in this case the professionals who take the pedagogical coordination, talking about this with their needs for initial and continuing training.